The Link Of Epstein Barr Virus Infection And Rheumatoid Arthritis Immunopathogenesis - Huriatul Masdar (Fakultas Kedokteran Universitas Riau, 2010)
The cause of Rheumatoid Arthritis (RA) remains unknown. Environmental factors as well as genetic factors have beenlinked to pathogenesis of RA, in particular Epstein Barr Virus (EBV) infection. Since clinical onset of RA is long timeafter primary viral exposure, it is still difficult to demonstrate the direct link of EBV infection with RA pathogenesis.However, the high levels of antibodies against several EBV proteins detected in RA patient sera, the molecular mimicryof EBV proteins with RA susceptible alleles, cross reactive of several antibodies against EBV with proteins in RAsynovium, the higher load of EBV in peripheral blood and synovial tissue of RA patients compared to non-RA patientsand EBV capability to induce ACPA production might show a clear link of EBV infection with RA pathogenesis.